SOCIAL EQUALITY AND INNOVATIVE APPROACHES TO DEVELOPING STUDENTS' DIGITAL LITERACY - Zumaeva , Zubaida (Uzbekistan Open Conference, 2025)
This article explores how the development of digital technologies affects students' digital literacy and highlights the role of digital inclusion and equity principles in ensuring equal access to digital resources. The author analyzes both international and national experiences in reducing the digital divide. Using Uzbekistan as a case study, the article discusses challenges, infrastructure, and future prospects based on scientific analysis.
Keywords: digital literacy; digital inclusion; digital inequality; innovations in education; information technologies; internet access; Uzbekistan’s experience; digital transformation; IT schools; artificial intelligence